The Effect of Starbo AFE and Probio FM Activators on the Quality of Water Hyacinth Compost (Eichornia crassipes) - Siregar, Ias Marroha Doli; Aritonang, Christian Yosua Salomo; Multazam, Zuhri (Sriwijaya Journal of Environment, 2025)
Water hyacinth (Eichhornia crassipes) is a weed that lives in water and has a high growth rate. It has the ability to increase evapotranspiration (evaporation and loss of water through plant leaves), reduce the amount of light entering the water, resulting in a decrease in the level of oxygen solubility in water, disrupt water traffic, and increase habitat for disease vectors. aquatic environment. A solution is needed to overcome this problem, one of which is by composting. In order for composting to take place faster, Starbo AFE and Probio FM activators are used which will provide good quality. this study aims to determine the effect of various activators on the nutrient content of water hyacinth compost, and to determine the best combination of activators on the nutrient content of water hyacinth compost. This research method uses one replication with three treatments (K1 K2 and K3 using Starbo AFE and Probio FM, and K0 without Starbo AFE and Probio FM). This study was conducted in two stages, namely the composting stage. The composting process was carried out for 30 days. Checks are carried out every 5 days in the form of turning and physical observation. After the composting process is complete, nutrient measurements are carried out. Characterization is carried out to determine the levels of C-Organic, N, P, K, and Aroma. The results of this study showed that Starbo AFE and Probio FM are effective against C-Organic, N and K levels and aroma in accordance with SNI.